Disseminated tumor cells as a monitoring tool for adjuvant therapy in patients with primary breast cancer - Gruber, Ines; Fehm, Tanja; Taran, Florin Andrei; Wallwiener, Markus; Hahn, Markus; Wallwiener, Diethelm; Krawzyck, Natalia; Hoffmann, Jürgen; Hartkopf, Andreas Daniel (Breast cancer research and treatment, 2014)
The presence of disseminated tumor cells (DTC) in the bone marrow (BM) of early breast cancer patients at initial surgery as well as during follow-up predicts an unfavorable outcome. This study aimed to assess whether adjuvant systemic therapy has the ability to eradicate DTC and to determine the clinical impact of DTC-persistence.